"A man's home is his castle and fortress": Effect of age on the psychological distress associated with house damage following super typhoon Haiyan. (March 2017) - Lavenda, Osnat; Hoffman, Yaakov; Grossman, Ephraim; Ben-Ezra, Menachem
Abstract: The devastating impact of losing one's home as a consequence of a disaster is a well-known fact. Nevertheless this impact have not been examined in different age groups. The present study aimed at examining the psychological distress following the aftermath of super Typhoon Haiyan among 1001 adults in their 20's and 40's. Psychological distress was affected by house-damage among adults in their 40's only, namely, one's house remaining intact provided a buffer against experiencing high levels of psychological distress. Adults in their 20's reported the same high level of distress regardless of house-damage. Results are interpreted in light of developmental models focusing on Burden and Resources perspectives. Highlights: Effects of age and house-damage on psychological distress was addressed. A significant interaction of Age X House-damage was obtained. Adults in their 20's had high distress regardless of house-damage. Adults in their 40's felt significantly less distress when their house was intact. Traumatic events may have different psychological meaning across the life span.